"Because they are connected": Linking structural inequalities in farmworker organizing. Issue 3 (November 2020) - Sbicca, Joshua; Minkoff-Zern, Laura-Anne; Coopwood, Shelby
Agriculture in the United States (US), long dominated by white male interests, is rooted in entrenched structural inequalities. Prominent among them is the power of growers over a dependable low-wage racialized and gendered workforce that is disciplined with the threat of their disposability. Workers and other activists have long responded with opposition. We advance radical food geography scholarship with a relational understanding of the structural inequalities that farmworkers experience and their resistance through farmworker movements, by centering the perspectives and experiences of activists with an intersectional praxis. We begin with a review of the compounding economic, political, and social inequalities experienced by farmworkers in the US in the context of xenophobic enforcement-first approaches to policing documented and undocumented Latinx immigrants. We then present a case study of Community to Community Development (C2C) in Washington state, an example of the radical frontlines of resistance by farmworker advocacy groups, as they link systems of oppression, especially with regard to class, immigration status, gender, and race. Ultimately, we argue for elevating more intersectional forms of organizing in the food system. In doing so, we encourage radical food geographers to conduct scholarship-activism more open to the many intersections between social position and structural inequality and resistance.